Management swing potential for bioenergy crops - Davis, S.C.; Boddey, Robert M.; Alves, Bruno J.R.; Cowie, A.L.; George, B.H.; Ogle, Stephen Michael; Smith, Pete; Noordwijk, Meine van; Wijk, Mark T. van (Wiley, 2013)
Bioenergy crops are often classified (and subsequently regulated) according to species that have been evaluated as environmentally beneficial or detrimental, but in practice, management decisions rather than species per se can determine the overall environmental impact of a bioenergy production system. Here, we review the greenhouse gas balance and ‘management swing potential’ of seven different bioenergy cropping systems in temperate and tropical regions. Prior land use, harvesting techniques, harvest timing, and fertilization are among the key management considerations that can swing the greenhouse gas balance of bioenergy from positive to negative or the reverse. Although the management swing potential is substantial for many cropping systems, there are some species (e.g., soybean) that have such low bioenergy yield potentials that the environmental impact is unlikely to be reversed by management. High-yielding bioenergy crops (e.g., corn, sugarcane, Miscanthus, and fast-growing tree species), however, can be managed for environmental benefits or losses, suggesting that the bioenergy sector would be better informed by incorporating management-based evaluations into classifications of bioenergy feedstocks